Can the Standard International Business Cycle Model Explain the Relation Between Trade and Comovement? - Yi, Kei-Mu (IMF Working Papers; Working Paper, 2005)
Recent empirical research finds that pairs of countries with stronger trade linkages tend to have more highly correlated business cycles. We assess whether the standard international business cycle framework can replicate this intuitive result. We employ a three-country model with transportation costs. We simulate the effects of increased goods market integration under two asset market structures, complete markets and international financial autarky. Our main finding is that under both asset market structures the model can generate stronger correlations for pairs of countries that trade more, but the increased correlation falls far short of the empirical findings. Even when we control for the fact that most country-pairs are small with respect to the rest of the world, the model continues to fall short. We also conduct additional simulations that allow for increased trade with the third country or increased TFP shock comovement to affect the country pair's business cycle comovement. These simulations are helpful in highlighting channels that could narrow the gap between the empirical findings and the predictions of the model.